Población venezolana en el contexto de la crisis sanitaria en Lima Metropolitana - Fernández Dávila, Rubén Ticona (2021)
This article addresses the issue of migration and the health crisis. Its objective is to identify the public policies adopted by Peru in response to the situation caused by the COVID-19 pandemic; it is analyzed from the perspective of population and development, the impact of the health crisis on the most vulnerable population groups, such as migrants. We maintain that the Venezuelan migrant population has been left in a situation of defenselessness in the face of the health crisis. Methodologically the article proposes a mixed analysis, combines analysis of statistical information, as well as discourse analysis and in-depth interviews. The results show not only the limited access of migrants to the public health system, but also the absence of State concern to address the problem. Finally, by way of conclusions, it affirms the need to know and recognize the problems faced by migrants in the country to increase the efficiency and effectiveness of the Peruvian State in the deployment of its public policies.